Question and Answers Forum

All Questions      Topic List

Relation and Functions Questions

Previous in All Question      Next in All Question      

Previous in Relation and Functions      Next in Relation and Functions      

Question Number 207314 by universe last updated on 11/May/24

 let f:R→R be a continuous function then   show that  (1) if  f(x) = f(x^2 ) ∀ x ∈R then f  is a constant    function   (2) if  f(x) = f(2x+1) ∀x∈R then f  is a     constant function

$$\:\mathrm{let}\:\mathrm{f}:\mathbb{R}\rightarrow\mathbb{R}\:\mathrm{be}\:\mathrm{a}\:\mathrm{continuous}\:\mathrm{function}\:\mathrm{then} \\ $$$$\:\mathrm{show}\:\mathrm{that} \\ $$$$\left(\mathrm{1}\right)\:\mathrm{if}\:\:\mathrm{f}\left(\mathrm{x}\right)\:=\:\mathrm{f}\left(\mathrm{x}^{\mathrm{2}} \right)\:\forall\:\mathrm{x}\:\in\mathbb{R}\:\mathrm{then}\:\mathrm{f}\:\:\mathrm{is}\:\mathrm{a}\:\mathrm{constant} \\ $$$$\:\:\mathrm{function} \\ $$$$\:\left(\mathrm{2}\right)\:\mathrm{if}\:\:\mathrm{f}\left(\mathrm{x}\right)\:=\:\mathrm{f}\left(\mathrm{2x}+\mathrm{1}\right)\:\forall\mathrm{x}\in\mathbb{R}\:\mathrm{then}\:\mathrm{f}\:\:\mathrm{is}\:\mathrm{a}\: \\ $$$$\:\:\mathrm{constant}\:\mathrm{function}\: \\ $$

Answered by Berbere last updated on 11/May/24

f(x)=f(x^2 )⇒f is continus  f(−x)=f(x)⇒  we show njst f∣[0,∞[ is constante  if x∈[0,1]   let p∈[0,1[ suchat that px∈[0,p[  ⇒f(px)=f(p^2 x^2 )=(p^2^n  x^2^n  );∀n∈N  f(px)=lim_(n→∞) f(p^2^n  x^2^n  )=f(0)  f(1−(1/n))=lim_(n→∞) f(1−(1/n))=0  =lim_(n→∞) f(0)=f(0)  if x>1  f((√x))=f(x)⇒∀n∈N^∗   f(x^(1/2^n ) )=f(x)⇒lim_(n→∞) f(x^(1/2^n ) )=f(lim_(n→∞) e^((1/2^n )ln(x)) )=f(1)=f(0)  ⇒∀x∈R f(x)=f(0)   2)  f(x)=f(2x+1)  x→^h 2x+1  hoh....h n times  =h^n (x)=a_n x+b_n   h^0 (x)=x=f(x)=2x+1  h^(n+1) =2a_n x+2b_n +1=a_(n+1) x+b_(n+1)   b_(n+1) =2b_n +1;a_(n+1) =2a_n ⇒a_n =2^n   b_n =2^n −1  h^n (x)=2^n x+2^n −1  ⇒y=2^n x+2^n −1;   x_n =(y/2^n )−1+(1/2^n )⇒f(x)=f(y) ;∀n y is fixed  f(y)=lim_(n→∞) f(((y+1)/(2^n  ))−1)=f(−1)   f is constante

$${f}\left({x}\right)={f}\left({x}^{\mathrm{2}} \right)\Rightarrow{f}\:{is}\:{continus} \\ $$$${f}\left(−{x}\right)={f}\left({x}\right)\Rightarrow\:\:{we}\:{show}\:{njst}\:{f}\mid\left[\mathrm{0},\infty\left[\:{is}\:{constante}\right.\right. \\ $$$${if}\:{x}\in\left[\mathrm{0},\mathrm{1}\right]\: \\ $$$${let}\:{p}\in\left[\mathrm{0},\mathrm{1}\left[\:{suchat}\:{that}\:{px}\in\left[\mathrm{0},{p}\left[\right.\right.\right.\right. \\ $$$$\Rightarrow{f}\left({px}\right)={f}\left({p}^{\mathrm{2}} {x}^{\mathrm{2}} \right)=\left({p}^{\mathrm{2}^{{n}} } {x}^{\mathrm{2}^{{n}} } \right);\forall{n}\in\mathbb{N} \\ $$$${f}\left({px}\right)=\underset{{n}\rightarrow\infty} {\mathrm{lim}}{f}\left({p}^{\mathrm{2}^{{n}} } {x}^{\mathrm{2}^{{n}} } \right)={f}\left(\mathrm{0}\right) \\ $$$${f}\left(\mathrm{1}−\frac{\mathrm{1}}{{n}}\right)=\underset{{n}\rightarrow\infty} {\mathrm{lim}}{f}\left(\mathrm{1}−\frac{\mathrm{1}}{{n}}\right)=\mathrm{0} \\ $$$$=\underset{{n}\rightarrow\infty} {\mathrm{lim}}{f}\left(\mathrm{0}\right)={f}\left(\mathrm{0}\right) \\ $$$${if}\:{x}>\mathrm{1} \\ $$$${f}\left(\sqrt{{x}}\right)={f}\left({x}\right)\Rightarrow\forall{n}\in\mathbb{N}^{\ast} \\ $$$${f}\left({x}^{\frac{\mathrm{1}}{\mathrm{2}^{{n}} }} \right)={f}\left({x}\right)\Rightarrow\underset{{n}\rightarrow\infty} {\mathrm{lim}}{f}\left({x}^{\frac{\mathrm{1}}{\mathrm{2}^{{n}} }} \right)={f}\left(\underset{{n}\rightarrow\infty} {\mathrm{lim}}{e}^{\frac{\mathrm{1}}{\mathrm{2}^{{n}} }{ln}\left({x}\right)} \right)={f}\left(\mathrm{1}\right)={f}\left(\mathrm{0}\right) \\ $$$$\Rightarrow\forall{x}\in\mathbb{R}\:{f}\left({x}\right)={f}\left(\mathrm{0}\right)\: \\ $$$$\left.\mathrm{2}\right) \\ $$$${f}\left({x}\right)={f}\left(\mathrm{2}{x}+\mathrm{1}\right) \\ $$$${x}\overset{{h}} {\rightarrow}\mathrm{2}{x}+\mathrm{1} \\ $$$${hoh}....{h}\:{n}\:{times} \\ $$$$={h}^{{n}} \left({x}\right)={a}_{{n}} {x}+{b}_{{n}} \\ $$$${h}^{\mathrm{0}} \left({x}\right)={x}={f}\left({x}\right)=\mathrm{2}{x}+\mathrm{1} \\ $$$${h}^{{n}+\mathrm{1}} =\mathrm{2}{a}_{{n}} {x}+\mathrm{2}{b}_{{n}} +\mathrm{1}={a}_{{n}+\mathrm{1}} {x}+{b}_{{n}+\mathrm{1}} \\ $$$${b}_{{n}+\mathrm{1}} =\mathrm{2}{b}_{{n}} +\mathrm{1};{a}_{{n}+\mathrm{1}} =\mathrm{2}{a}_{{n}} \Rightarrow{a}_{{n}} =\mathrm{2}^{{n}} \\ $$$${b}_{{n}} =\mathrm{2}^{{n}} −\mathrm{1} \\ $$$${h}^{{n}} \left({x}\right)=\mathrm{2}^{{n}} {x}+\mathrm{2}^{{n}} −\mathrm{1} \\ $$$$\Rightarrow{y}=\mathrm{2}^{{n}} {x}+\mathrm{2}^{{n}} −\mathrm{1};\: \\ $$$${x}_{{n}} =\frac{{y}}{\mathrm{2}^{{n}} }−\mathrm{1}+\frac{\mathrm{1}}{\mathrm{2}^{{n}} }\Rightarrow{f}\left({x}\right)={f}\left({y}\right)\:;\forall{n}\:{y}\:{is}\:{fixed} \\ $$$${f}\left({y}\right)=\underset{{n}\rightarrow\infty} {\mathrm{lim}}{f}\left(\frac{{y}+\mathrm{1}}{\mathrm{2}^{{n}} \:}−\mathrm{1}\right)={f}\left(−\mathrm{1}\right)\: \\ $$$${f}\:{is}\:{constante}\: \\ $$$$ \\ $$$$ \\ $$$$ \\ $$$$ \\ $$

Commented by universe last updated on 11/May/24

thank u sir

$${thank}\:{u}\:{sir} \\ $$

Commented by Berbere last updated on 11/May/24

Withe Pleasur

$${Withe}\:{Pleasur} \\ $$$$ \\ $$

Terms of Service

Privacy Policy

Contact: info@tinkutara.com